Implementasi Visual Manajemen Terhadap Kegiatan Operasional dan Keamanan Laboratorium Biokimia - S Soesilowati (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
Management implementation is a form of regulation in conveying information visually with the aim that everyone can understand the situation and conditions in the laboratory area. Visual management implementation uses the 5R principle in its application, namely concise, neat, clean, careful and diligent so as to produce habits that make it a culture to carry out activities in the laboratory according to operational standards. This study aims to determine the level of efficient performance in the operation and safety of the biochemical laboratory. Testing is carried out by identifying the layout of the laboratory interior including tools and materials, planning, compiling, socializing and implementing SOP and K3 in activities in the biochemical laboratory.